VD_FINDINFO Décision / 2014 / 696 vom 18. August 2014 - VD Tribunal cantonal (2014)
AVOCAT, DÉPENS, DOMMAGE PATRIMONIAL, TORT MORAL | 429 al. 1 let. a CPP (CH), 429 al. 1 let. b CPP (CH), 429 al. 1 let. c CPP (CH), 448 al. 1 CPP (CH)